Analisis Pengaruh Produksi Gula Merah terhadap Tingkat Pendapatan Petani Gula Merah di Kampung Nubuai Distrik Urei Faisei Kabupaten Waropen - Virgilio C Meliala; Waspada Meliala; Pieter N de Fretes; Jhon Ayomi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to determine the level of income earned by palm sugar (brown sugar) producers in Nubuai Village, Urei Faisei District, Waropen Regency. The research employed a descriptive research design. The population consisted of all palm sugar farmers in Nubuai Village, Urei Faisei District, Waropen Regency. The sampling technique used was purposive sampling, with a total sample of 10 respondents. The data sources included primary and secondary data. Primary data were obtained through direct interviews conducted by the researcher using a structured questionnaire containing previously prepared questions. Secondary data were collected from relevant government institutions related to the study. Data collection techniques included observation, questionnaires, and documentation. Data analysis was carried out using multiple regression analysis, t-test, and F-test. The results showed that the income variable obtained by palm sugar producers had a positive and significant effect on the income of palm sugar farmers in Nubuai Village, Urei Faisei District, Waropen Regency, with a regression coefficient value of Rp 8,976.001 and a significance value of 0.000 < 0.05. The farmers’ revenue variable also had a positive and significant effect on farmers’ income in Nubuai Village, with a regression coefficient value of Rp 15,791.849 and a significance value of 0.038 < 0.05. Furthermore, the variables of experience and palm sugar price simultaneously influenced the income of palm sugar farmers in Nubuai Village, Urei Faisei District, Waropen Regency.